A fuzzy DEMATEL based sustainable development index (FDSDI) in open pit mining – a case study (Rudarsko-geološko-naftni zbornik, 2019)
As an economic activity, mining can have positive and negative effects for the community. These negative impacts along with some of the social, economic, and environmental impacts of mining actions threaten the achievement of sustain- able development (SD) goals. Therefore, an impact evaluation of SD indexes is significant for protecting mining actions in line with the objectives of SD. For that reason, a system classification was proposed with the use of the fuzzy decision- making trial and evaluation laboratory (fuzzy DEMATEL) technique to study and analyse eleven impacting factor inter- relationships in open pit mines. Since this technique is based upon the opinion of experts, the fuzzy coding technique was used. In this manner, the weight of the impacting factors and their related ratings were chosen to develop a new classification system. Based on the proposed rating system, FDSDI was introduced to describe system-levels qualita- tively and quantitatively. The application of FDSDI was investigated in a bauxite mine as a case study. The results show that FDSDI is an easy and effective tool to evaluate sustainability in bauxite mining. Generally, the conducted technique presents a systematic approach for holistic analysis of the impacting factors of SD in open pit mines.